Exploring earnings management: Institutional ownership and audit size in Malaysia’s sustainability pathway - Ali, Salsiah Mohd; Norhashim, Mariati; Jaffar, Nahariah (International Journal of Management and Sustainability, 2023)
This study aims to investigate the relationships between discretionary accrual earnings management (DEM), real earnings management (REM), institutional ownership, and audit quality in Malaysian firms. The study’s findings are expected to offer insights into how these factors may influence Malaysia’s progress towards the Sustainable Development Goals. We examine the relationship between DEM and REM to identify the potential simultaneous use of earnings management strategies. Additionally, we explore the impact of institutional ownership and audit firm size on a company’s earnings management practices. Using data from the Kuala Lumpur Stock Exchange (KLSE) spanning 2016-2018 we conducted statistical analyses, including ANOVA, t-tests, and multiple regression. There were notable correlations between DEM and REM, suggesting that these earnings management techniques are being used concurrently. Notably, institutional ownership and audit firm size played substantial roles in firms’ earnings management practices. Companies with higher institutional ownership and larger audit firms tended to exhibit lower levels of DEM and REM. However, these factors did not appear to moderate the DEM-REM relationship. These findings have critical implications for regulators and policymakers in addressing earnings management practices and enhancing corporate governance in Malaysia. Focusing on institutional ownership and audit firm size may help curtail such practices, contributing to Malaysia’s progress towards the Sustainable Development Goals. Future research should explore other potential moderating variables and distinctive corporate governance features that could also impact the DEM-REM relationship.